2008
DOI: 10.1159/000149901
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Cutaneous Lesions with Clinical Radiological and Urodynamic Findings in the Prognosis of Underlying Spinal Dysraphism Disorders

Abstract: Spinal dysraphism is characterized by a lack of fusion of the vertebral arches that occurs in the absence of spinous processes with variable amounts of lamina. Here, we retrospectively present the importance of cutaneous lesions and their correlation with clinical presentation, radiological examination and urodynamic assessment. We retrospectively reviewed 612 (6.12%) cases with skin lesions from 10,000 consecutive live-born children seen at two institutions between January 1998 and March 2005. We divided all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 71 publications
(45 reference statements)
0
10
0
1
Order By: Relevance
“…Supporting this view, Sasani et al used ultrasound, MRI, or both to examine 264 subjects with sacral dimples (Table 3) and found 41 cases (15.5%) of tethered cord, including 21 with thickened and fatty terminal fila, 16 with dermal sinuses, 3 with diastematomyelia, and 1 with lipomyelomeningocele. 16 There was a discordance of 16.6% between ultrasound and MRI, with ultrasound often failing to detect abnormalities. Thus, the authors concluded that MRI is preferable for evaluating spinal disorders in neonates.…”
Section: 19mentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this view, Sasani et al used ultrasound, MRI, or both to examine 264 subjects with sacral dimples (Table 3) and found 41 cases (15.5%) of tethered cord, including 21 with thickened and fatty terminal fila, 16 with dermal sinuses, 3 with diastematomyelia, and 1 with lipomyelomeningocele. 16 There was a discordance of 16.6% between ultrasound and MRI, with ultrasound often failing to detect abnormalities. Thus, the authors concluded that MRI is preferable for evaluating spinal disorders in neonates.…”
Section: 19mentioning
confidence: 99%
“…10,16 In clinical practice, however, it is important to distinguish between dermal sinus tracts and sacrococcygeal dimples, as they are treated differently. The dural sac ends at S-2, 8 and sacrococcygeal dimples do not extend into the intradural space.…”
Section: 19mentioning
confidence: 99%
“…[39][40][41] Among surgical studies (n = 12), there was no clear or standardized description in the untethering technique utilized. [30][31][32][33][34]37,38,[42][43][44] Among these surgical studies, only 6 described their complications in the results section of the respective article. Additionally, 5 out of the 13 studies did not provide information on the length of follow-up after surgical intervention.…”
Section: Description Of Evaluation Results and Follow-upmentioning
confidence: 99%
“…In our systematic review, we observed differences in the diagnostic criteria of TCS and widely variable health outcomes following surgery in Asian countries. 31,[38][39][40] Our findings suggest that among studies conducted in this region, the management of TCS was aggressive in the surgical approach leading to untethering and often did not rely on the pres-ence of progressive neurologic deficits as a criterion for initial surgical treatment of spinal cord tethering. 30,33,34,42 To address the observable variation in the diagnostic criteria for TCS, Lew and Kothbauer 26 defined TCS as "a diverse clinical entity which presents with symptoms and signs resulting from abnormal spinal cord tension. "…”
Section: Global Surgery and Variance In Surgical Approach To Tcsmentioning
confidence: 90%
See 1 more Smart Citation